Relationship between periparturient diseases, metabolic markers and the dynamics of hair cortisol concentrations in dairy cows. (May 2023) - Tekin, M.; Câmara, D.R.; Binz, T.M.; Bruckmaier, R.M.; Bollwein, H.; Wagener, K.
Abstract: Hair cortisol concentration (HCC) might represent a promising marker for retrospective welfare assessment of dairy cows. The objective of the study was to explore the dynamics of HCC in diseased and healthy cows from eight-week ante partum (AP) to eight-week post partum (PP). Twenty-four pregnant cows were followed from drying off to week eight PP. Tail hair was used to measure cortisol at five different time points. The occurrence of peripartum diseases, lameness and the body condition score (BCS) were monitored on a weekly basis. Blood β-hydroxybutyric acid, non-esterified fatty acids, calcium and insulin-like growth factor-1 (IGF-1) concentrations were measured. The temperature-humidity index (THI) was continuously recorded. The median values of HCC in all cows were 0.4, 0.3, 0.6, 0.8 and 0.5 pg/mg at weeks eight, four AP, calving, weeks four, eight PP, respectively. There was no association between HCC and the occurrence of peripartum diseases ( P  ≥ 0.05). A positive correlation between HCC and BCS loss ( P  < 0.01) and THI ( P  < 0.05) was observed. The occurrence of peripartum diseases was associated with low IGF-1 during the study period but no relationship was found between cortisol and IGF-1 levels ( P  ≥ 0.05). Brown Swiss cows showed higher HCC ( P  < 0.01) at weeks eight, four AP, and week four PP and lower average milk yield ( P  < 0.05) than Holstein–Friesian cows. In conclusion, HCC was not a suitable marker for peripartum diseases but it could reflect a stress response, which is linked to BCS loss, heat stress and breed. Highlights: There was no association between hair cortisol concentration (HCC) and diseases. Brown Swiss cows had higher HCC and lower milk yield than Holstein-Friesian cows. A positive correlation was found between HCC and body condition loss. No relationship was found between HCC and IGF-1 concentrations. HCC could reflect a stress response linked to BCS loss, heat stress and breed.